Hamka's Thoughts on Women's Education: Analysis of Al-Azhar's Interpretation (Surah An-Nisa': 34-35) - Achmad Hikmatiyar; Muhammad Arfan Mu’ammar; Zainal Arifin (Eduvest - Journal of Universal Studies, 2024)
This research discusses Hamka's thoughts, especially on Surah An-Nisa' 34-35, regarding women's education within the family sphere. The role of women as primary educators in the family is the main focus. The aim of this research is to analyze Hamka's thoughts on the role of women in the family, their responsibilities in supporting their husbands as family leaders, and their contributions to building a household. The methodology employed in this research is a qualitative approach using literature review methods to gather data from various literary sources, which are then analyzed using inductive approaches and content analysis techniques. Additionally, this research discusses women's rights related to education and teaching, as well as their right to demand justice within the family, in line with Islamic values and Indonesian government regulations. In his thoughts, Hamka emphasizes that women have responsibilities within the household and must obey their husbands as leaders, but they also have the right to participate in society and have access to education and justice, in accordance with Islamic principles and applicable legal regulations.